Developmental Trajectories in Very Preterm Born Children Up to 8 Years: A Longitudinal Cohort Study - van Beek, Pauline E.; van der Horst, Iris E.; Wetzer, Josse; van Baar, Anneloes L.; Vugs, Brigitte; Andriessen, Peter (Frontiers in Pediatrics, 2021)
Aim: Long-term outcome data in preterm children is often limited to cross-sectional measurement of neurodevelopmental impairment (NDI) at the corrected age of 24-36 months. However, impairments may only become overt during childhood or resolve with time, and individual trajectories in outcome over time may vary. The primary aim of this study was to describe NDI in very preterm born children at three subsequent ages of two, five and eight years of age. As a secondary aim, a longitudinal analysis was performed on the individual longitudinal trajectories in NDI from two to eight years of age. Methods: Single-center prospective cohort study including children born between 1990 and 2011 below 30 weeks’ gestation and followed into 2019. The outcome measurement was NDI assessed at two, five and eight years of age. NDI is a composite score that includes cognitive, neurological, visual and auditory functions, in which problems were categorized as none, mild, moderate or severe. Cognitive function measured as total DQ/IQ score was assessed by standardized psychometric tests. Neurological, visual and auditory functions were assessed by the neonatologist. Results: In total, 921 children were eligible for follow-up, of whom 726 (79%) children were assessed. No NDI was seen in 54%, 54% and 62%, mild NDI was seen in 31%, 36% and 30%, and moderate-to-severe NDI was seen in 15%, 9.2% and 8.6% of the children at two, five and eight years, respectively. From two to eight years, 63% of the children remained in the same NDI category, 20% of the children improved to a better NDI category and 17% deteriorated towards a worse NDI category. No differences were found in baseline characteristics of infants that improved or deteriorated. Extreme prematurity, male gender and low parental education were associated with worse NDI status at all time points. Although we observed considerable individual variation over time in NDI status, the course of the trajectories in NDI were not associated with gestation, gender and parental education. Conclusions: Continued follow-up until school life is essential in order to provide optimal and individually focused referrals and care when needed.